Rehabilitasi Sistem Pompa Irigasi untuk Menjamin Ketersediaan Air pada Lahan Pertanian di Gampong Limpong, Kecamatan Darussalam - Ali, Nurdin; Suhaeri; Husaini; Arhami; Putra, T. Edisah; Aulia, Udink; Syahriza; Bakhtiar, Dandi; Sabri (Yayasan Kawanad, 2024)
The rehabilitation of irrigation pumps plays a crucial role in ensuring sufficient water availability for rice fields in Gampong Limpong, Darussalam District. A significant challenge faced by farmers in this region is the malfunctioning of irrigation pumps, which leads to suboptimal water distribution. This issue directly affects agricultural productivity and the welfare of farmers. Through rehabilitation efforts, damaged pumps are either repaired or replaced with more efficient units. The rehabilitation process involves the identification of damages, repair of key components, and operational trials to verify optimal pump performance. Results from this initiative indicate a more stable availability of irrigation water, thereby enhancing crop yields for farmers. This rehabilitation not only offers technical solutions but also fosters active community involvement in maintaining the sustainability of the irrigation system. Consequently, this program contributes positively to the development of the agricultural sector in Gampong Limpok.